2018
DOI: 10.5588/ijtld.17.0069
|View full text |Cite
|
Sign up to set email alerts
|

Allergen sensitisation among chronic respiratory diseases in urban and rural areas of the south of Viet Nam

Abstract: Dust mites and cockroach droppings were the most frequent allergens among people with CRD in the south of Viet Nam. Compared with the urban population, being native to a rural area was protective against mite sensitisation, but this effect ceased to be significant after migration from rural to urban areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 0 publications
2
16
1
Order By: Relevance
“…The high prevalence of dust mite sensitization was consistent with previous studies in Vietnam [ 8 9 17 ]. Consistently with our data, a recent study in northern Vietnam reported a prevalence of sensitization by SPT of 23%, 13%, and 13% to Blo t, Der p, and cockroach, respectively, while sensitization was not associated with asthma [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The high prevalence of dust mite sensitization was consistent with previous studies in Vietnam [ 8 9 17 ]. Consistently with our data, a recent study in northern Vietnam reported a prevalence of sensitization by SPT of 23%, 13%, and 13% to Blo t, Der p, and cockroach, respectively, while sensitization was not associated with asthma [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…Both active and suspected tuberculosis patients were excluded by routine chest X-ray and microbial sputum analysis. After obtained informed written consent, a lung function test (LFT) was measured [ 9 ] while blood sampling and SPT were performed after stopping antihistamines at least 5 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of allergic sensitization is rising in developing countries, 1 a phenomenon related to rapid urbanization 2 , 3 . In Vietnam, preliminary data suggest that an adult's migration from a rural to an urban area increases their risk of sensitization to mite allergens 4 that could contribute to a rapid increase of chronic respiratory diseases (CRD), which is one of the priorities of public health in Vietnam 5 . Compared to rural life, urban life is characterized by different outdoor and indoor pollution, disappearance of gut parasitosis, occupational factors, and food habits.…”
Section: Introductionmentioning
confidence: 99%